IMPACT OF SUPPLYING SOME SAFE NATURAL HONEY BEE PRODUCTS ON THE PRODUCTION OF FENNEL PLANTS - Abou-Sreea, Alaa I. B.; Roby, Mohamed H. H.; Ahmed, Safia M. A. (Acta Scientiae et Intellectus, 2024)
Honey bee products as propolis (Pp) and Royal jelly (RJ) are natural mixture and powerful source of safe nutrients that could be used in agriculture safely as substitution of poisonous and dangerous chemical fertilizers. The impact of using them either solely or in interaction as foliar application on some Fennel morphological traits, seed (fruit) yield, oil production and its main components and chemical constituents has been investigated in a field research during (2017/2018 and 2018/2019) at the Experimental farm in Faculty of agriculture, fayoum University. RJ and Pp were foliary sprayed at three rates 0.0, 0.2, 0.4% and 0, 3, 6 gL-1 respectively in sole and interaction treatments. All records assured that the application of both materials (RJ, Pp) have a positive useful impact on all traits studied either used individually or in interaction. The moderate concentrations of both materials individually or interaction (0.2 % RJ, 3 gL-1 Pp) gave the highest records of growth and yield characters and Anethole compared with other treatments with more superiority of Rj results over those of Pp in sole treatments even though Rj concentration is less than that of Pp especially in oil percentage and umbels number. On the other side, the highest concentration of either Rj (0.4%) or moderate one of Pp (3 gL-1) as sole treatment or in combination gave the highest records of most chemical composition. As well as 0.4% Rj with 6 gL-1 Pp produced the highest percentage of Estragole. Hence, fennel plants can be safely grown and highly produced by these safe natural materials without the help of the poisonous chemical fertilizers.